DETERMINANTS OF FIRM VALUE IN TRANSPORTATION COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Zain, Maulana Daffa'; Andhaniwati, Erry (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to assess the influence of financial performance variables (X2) and good governance variables (X1) on financial value (Y) in the context of 36 publicly traded transportation companies listed on the Indonesian Stock Exchange from 2018 to 2022. Purposive sampling was employed, resulting in a sample of 21 companies that met the study criteria. Analysis was conducted using the partial least squares (PLS) method with SmartPLS 3.0 software. The findings indicate that both financial performance and good governance significantly contribute to enhancing company value. Specifically, improved financial performance positively impacts financial value, while effective corporate governance practices also play a crucial role in increasing company value. These results underscore the importance of integrating robust financial strategies and governance frameworks to optimize organizational performance and investor perception in the transportation sector